Perspectivas antropológico-cristãs: elementos de uma antropologia cristã na Evangelii Gaudium - Graciani, Maria Regina Ribeiro (2016)
This research presents a study of the human being from the perspective of Christian anthropology. It is through the central mystery of the life of Jesus Christ, the Son of the living God, in his Incarnation, Passion, Death and Resurrection, which reveals the divine plan for humanity. The Christian faith points out that the encounter between God and human happens unsurpassed way in Jesus Christ and, through Him, and the grace of the Spirit, the human being has the possibility of conformity to God and to share in his divine life. The relationship with God is essential for the achievement of every man, every woman and all mankind. In the Apostolic Exhortation Evangelii Gaudium, Pope Francis makes a swing state in which humanity faces today and is an invitation for a return and deepening the encounter with Jesus Christ. It proposes that the joy, the strength of the Risen Lord, is present in the practice of the law of love and shine more in the daily life of Christians and from them to the society. The message of life proclaimed and lived for twenty-one centuries by Master's followers still present in preaching and life of Christians today. It is the joy of the Gospel that illuminates and gives meaning to human life, as evidenced by the Holy Scriptures: "I have come that they may have life and have it abundantly" (Jo 10,10)